Vascular trauma in Western Australia: a comparison of two study periods over 15 years. Issue 3 (16th July 2013) - Friend, Jikol; Rao, Sudhakar; Sieunarine, Kishore; Woodroof, Paul
Abstract: Background: Royal Perth Hospital (RPH) has become Western Australia's only designated adult major trauma facility since a previous study of vascular trauma was conducted in 2001 at the same facility. The aim of this study is to identify changes in vascular trauma patterns over the two study periods and compare these changes with international literature. Methods: All individuals presenting to RPH between January 2000 and December 2010 with vascular injury were identified from a prospective trauma database for this descriptive study. Injuries were classified using the Abbreviated Injury Score (AIS). Results: The incidence of vascular trauma as a percentage of total trauma increased over the two study periods. The current 10‐year study included 45 164 patients on the trauma database, of which 1205 patients (2.6%) sustained 1335 vascular injuries, an increase from 1% in the previous 5‐year study at the same facility. Males aged 20–29 years were more frequently injured. Blunt trauma occurred more frequently than penetrating. The extremities, particularly the upper limbs were most commonly injured. The most common causes of injury for each region were as follows; motorbike crash (MBC), motor vehicle crash (MVC) and stabbing (neck, thorax and abdomen), MBC and MVC (lower limb) and piercing injuries (upper limb). Injury Severity Score (ISS) and mortality 43% (32 of 75) were highest for thoracic injuries, particularly thoracic aorta injury. Mortality rate has decreased. Conclusion: Vascular injuries in Western Australia are increasing. MVC are the most common cause of life threatening injury. Road safety interventions targeting young males are likely to reduce trauma.